2018
DOI: 10.1177/1029864918780186
|View full text |Cite
|
Sign up to set email alerts
|

Music listening as a potential aid in reducing emotional eating: An exploratory study

Abstract: Emotional Eating (EE) is understood as a maladaptive self-regulation strategy to satisfy emotional needs instead of hunger. Consequently, EE has been associated with negative health consequences.Enjoyment of food and music share similar neural activations in the brain and are both used by people for regulating affect. This suggests that music listening could potentially be a healthier alternative to EE. The present study was designed to investigate associations between EE, disordered mood, and music-related mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 70 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, maladaptive coping strategies, which included the subscales behavioural disengagement, self-blame and low acceptance, were associated with emotional and uncontrolled eating prior to lockdown. This suggests that these eating behaviours are part of a wider set of coping strategies, whereby, these types of eating behaviours may be part of a toolbox of maladaptive coping strategies, which worsen behaviours in time of distress ( Cheng et al, 2014 ; Van den Tol et al, 2018 ). Evers et al (2010) found that individuals who were asked to supress cognitions, which is viewed as a maladaptive strategy, ate more foods following an emotion induction than those using other strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, maladaptive coping strategies, which included the subscales behavioural disengagement, self-blame and low acceptance, were associated with emotional and uncontrolled eating prior to lockdown. This suggests that these eating behaviours are part of a wider set of coping strategies, whereby, these types of eating behaviours may be part of a toolbox of maladaptive coping strategies, which worsen behaviours in time of distress ( Cheng et al, 2014 ; Van den Tol et al, 2018 ). Evers et al (2010) found that individuals who were asked to supress cognitions, which is viewed as a maladaptive strategy, ate more foods following an emotion induction than those using other strategies.…”
Section: Discussionmentioning
confidence: 99%
“…EE is much more common in individuals who have overweight or obesity ( Peneau, Menard, Mejean, Bellisle, & Hercberg, 2013 ), and worries about weight gain as a result of EE can lead to feelings of guilt ( Dubé, LeBel, & Lu, 2005 ; Macht & Dettmer, 2006 ) and thereby potentially even cancelling out the short-term reduction in negative effect. It has additionally been found that those people who report a larger variety of strategies for coping with aversities have better mental health in general and are also less likely to report to engage in EE ( Cheng, Lau, & Chan, 2014 ; Van den Tol, Coulthard, & Hanser, 2018 ) and found that eating is generally reported by people to be the least successful strategy for changing a bad mood ( Thayer, Newman, & McClain, 1994 ) out of a number of affect regulation behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the functionality of ironically enjoyed music draws more on it possessing aspects of genuine enjoyment (e.g., even if a dance song is seen as “cheesy” it is emotionally engaging and “novel”). Future research could further explore these findings with stronger causal inference, taking into account findings on the links between music selection strategies and the functions of music listening (Baltazar & Saarikallio, 2016, 2019; Van den Tol, Coulthard, & Hanser, 2016; Maher, van Tilburg, & van den Tol, 2013; Van den Tol & Edwards, 2014; Van den Tol, Edwards, & Heflick, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…2 This data was part of a data set that has been used in previous publications (Van den Tol, Coulthard & Hanser, 2018).…”
Section: Footnotesmentioning
confidence: 99%
“…Recent research (Van den Tol, Coulthard & Hanser, 2018) investigated the association between the use of different music listening strategies, EE and symptoms of stress (as well as anxiety and depression). It was found that the use of music for discharge was positively associated with EE, and both EE and the use of music for discharge were positively associated with stress.…”
Section: Introductionmentioning
confidence: 99%